The Effect of Profitability and Liquidity on Firm Value with Dividend Policy as a Mediating Variable in Automotive Companies Listed on The Indonesian Stock Exchange - Torusan Lumban Gaol; Imam Wibowo; Munawaroh (Krisnadwipayana International Journal of Management Studies, 2024)
The purpose of this study is to analyze the effect of profitability and liquidity on firm value by using dividend policy as a mediating variable in automotive companies listed on the Indonesia Stock Exchange (IDX). The information is obtained from the website www.idx.co.id and from automotive companies that are the subject of research. The research lasted for eight months, from August 2023 to March 2024, and quantitative methods were used to test the hypothesis through statistical analysis. This type of research is explanatory research that analyzes the relationship between variables to test existing theories or hypotheses. The data analysis technique used to determine the mediating variable is panel data regression and path analysis. The results showed that the t-score (1.240) was lower than the t-table (2.026), so the mediation coefficient was not significant, indicating that dividend policy did not mediate the relationship between profitability and firm value. The results of the analysis show that profitability has a positive and significant effect on firm value; The higher the profit, the higher the firm value. While liquidity has a negative and significant effect; The higher the liquidity, the lower the firm value. An increase in profitability supports dividend policy by increasing the availability of funds, while an increase in liquidity causes companies to choose investment over paying dividends. In summary, it can be said that dividend policy does not mediate the relationship between profitability and firm value, but can mediate the relationship between liquidity and firm value